2016
DOI: 10.1186/s13007-016-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a universal and simplified ddRAD library preparation approach for SNP discovery and genotyping in angiosperm plants

Abstract: BackgroundThe double digest restriction-site associated DNA sequencing technology (ddRAD-seq) is a reduced representation sequencing technology by sampling genome-wide enzyme loci developed on the basis of next-generation sequencing. ddRAD-seq has been widely applied to SNP marker development and genotyping on animals, especially on marine animals as the original ddRAD protocol is mainly built and trained based on animal data. However, wide application of ddRAD-seq technology in plant species has not been achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 45 publications
0
63
0
1
Order By: Relevance
“…The addition of 24 adapters with barcodes in the ligation step allowed the pooling of samples and the application of size selection before PCR, as reported in ddRADseq [9]. Moreover, the use of different barcode lengths (4 to 9 bp, Poland et al [27]) allowed us to avoid sequencing phasing error at the beginning of reads, as reported in GBS and MiddRADseq [3,17], but not considered in the original ddRADseq [9]. For this scaled-up P2, we also proposed the use of automatic size selection, which would decrease the possibility of cross-contamination and increase the precision and consistency when applying the protocol for more than one pool of samples [5], as reported in the original ddRADseq [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of 24 adapters with barcodes in the ligation step allowed the pooling of samples and the application of size selection before PCR, as reported in ddRADseq [9]. Moreover, the use of different barcode lengths (4 to 9 bp, Poland et al [27]) allowed us to avoid sequencing phasing error at the beginning of reads, as reported in GBS and MiddRADseq [3,17], but not considered in the original ddRADseq [9]. For this scaled-up P2, we also proposed the use of automatic size selection, which would decrease the possibility of cross-contamination and increase the precision and consistency when applying the protocol for more than one pool of samples [5], as reported in the original ddRADseq [9].…”
Section: Discussionmentioning
confidence: 99%
“…Ligation: 24 variable-length (4 to 9 bp) barcodes designed by Poland et al [30] were added, in order to avoid low sequence quality of the first bases due to the restriction site [3,17] (Supplementary Table S2).…”
Section: Protocol 2 (P2): Optimized Ddradseq (Scaling Up To 24 Samples)mentioning
confidence: 99%
See 1 more Smart Citation
“…2) was required in our library preparation for the two tested systems, which could open the possibility of using ddRADseq technique with low quantity DNA template from non-invasive sampling in a conservation genomics context. If the initial protocol from Peterson et al (2012) already suggested to use less than 100 ng of DNA per individual, ddRADseq users commonly process more than 200 ng and even up to 1 μg (Capblancq et al, 2015; Yang et al, 2016; Burns et al, 2017; Sherpa, Rioux, Goindin, et al, 2018). Here we showed that enzyme saturation can already happen at the digestion step with 250 ng.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the trade-off existing between a satisfactory coverage, directly related to the number of PCR cycles, and the limitation of errors occurring during PCR, because these can lead to very weak fragment coverage impeding loci reconstruction (Hohenlohe et al, 2012). Usually the number of PCR cycles is set between 12 and 16 (Peterson et al, 2012; Capblancq et al, 2015; Yang et al, 2016; Burns et al, 2017). Considering the important increase in individual heterozygosity and number of private alleles observed with 25 PCR cycles, our results greatly support this practice.…”
Section: Discussionmentioning
confidence: 99%